Un modelo geodésico para Colombia - Sánchez Rodríguez Laura Marlene; Rocha A. Germán A.; Martínez Díaz William Alberto (Earth Sciences Research Journal)
The processed gravimetric information is compiled in the SIMPLE BOUGUER GRAVITY ANOMALY MAP OF COLOMBIA, EASTERN PANAMA AND ADYACENT MARINE AREAS, published in 1989 by The Geological Society of America Inc. Based on Isostatic anomaly values (approximated) obtained for difference between the observed Simple Bouguer anomaly values and itself, processed by means of the Bidimensional Fourier Transform, the Physical-Mathematical Stokes model was applied. With this model can be possible to determine the geoid undulations, relating the normal gravity, the anomaly potential and the gravity anomalies; these undulations are based on the WGS-84 ellipsoid. La información gravimétrica procesada esta compilada en el Mapa de anomalía Bouguer simple de Colombia, este de Panamá y aéreas marinas adyacentes, publicado por “The Geological Society of America Inc.” en 1989. A partir de los valores de la anomalía isostática (aproximada), resultante de la diferencia entre la anomalía Bouguer simple observada y la misma, procesada por medio de la Transformada de Fourier Bidimensional, se aplicó el modelo físico-matemático de Stokes, con el cual se determinan las ondulaciones geoidales relacionando la gravedad normal, el potencial anómalo y las anomalías de la gravedad; tales ondulaciones se referenciaron al elipsoide WGS-84.